INCOME TRANSFER PROGRAM IN BRAZIL AS A STRATEGIC MECHANISM FOR THE ERADICATION OF CHILD LABOR - Cardozo dos Santos, Sônia Maria; Nery da Silva, Rogério Luiz (Unoesc International Legal Seminar, 2017)
This article aims at presenting reflections on the relation existing between Child labor and the income transfer program in Brazil (Programa Bolsa Família). The present research has its relevance considering that Child labor represents a barrier for education, health, child-juvenile development, and it is characterized, many times, as a form of violence against children and adolescents. The requirement of school frequency for the beneficiaries of the Program Bolsa Família aims at expanding the possibilities for the effectiveness of education rights, as well as preventing precocious labor and its consequences. Within this study, through the appliance of deductive comparative method, from bibliographic sources and patterns concerning the theme of research, it was possible to explore the problem consisting in the relation between Child labor and the income transfer program in Brazil trabalho as well as its effectiveness for the decrease and eradication of illegal work in such an early age. In order to accomplish the objective of the research, this article was divided into two main topics: "Child labor: violence against children and adolescents" and "Program of Income Transfer in Brazil as a strategy for the eradication of Child labor: Program Bolsa Família".